Radical Scavenging Activity of Thymbra spicata and Quercus ithaburensis in a Fenton Reagent Environment and Their Protective Effects on Unsaturated Fatty Acids - Yilmaz, Okkes; Akkaya, Hatice (Foundation Environmental Protection & Research-Fepr, 2012)
In this study, the aim is to investigate the preventive effects of T. spicata and Q. ithaburensis extracts on lipid peroxidation (LPO) formation and unsaturated fatty acids in a Fenton reagent environment. The in vitro experiments were divided into four groups, the first group being the control, the second group Fenton's reagent (FeCl2+H2O2, Fenton R), the third group Fenton's reagent plus T. spicata extracts, and the fourth group Fenton's reagent plus Q. ithaburensis extracts. According to the experimental results, while the LPO level in the T. spicata group partially decreased (p<0.05), the LPO level in the Q. ithaburensis group was distinctly high (p<0.001) compared to the control group. The LPO level in the Fenton R group when compared to the T. spicata group, increased ten-fold (p<0.0001), where the Q. ithaburensis group decreased by 50% (p<0.001). When the DPPH radical scavenging activity of the extracts of T. spicata and Q. ithaburensis were examined, they were found to be as effective as quercetin (p<0.05) The fatty acid levels were analyzed for the in vitro environment, the amount of fatty acids in the T. spicata and Q. ithaburensis groups were higher than that of the Fenton R group (p<0.001). Our test results confirm that T. spicata and Q. ithaburensis extracts decreased the LPO level in the Fenton reagent containing environment and they noticeably protect the unsaturated fatty acids in the environment from radical sourced oxidations.
Thymbra spicata ve quercus i?thaburensis'in, fenton reaktifi ortamında radikal temizleme aktiviteleri ve doymamış ya? asitleri üzerindeki koruyucu etkileri
Keywords: Fenton reagent (Fenton R); flavonoids; lipid peroxidation (LPO); radical scavenging effects; T. spicata L.; Q. ithaburensis Decne